Positive effect of microvascular proliferation on functional recovery in experimental cervical spondylotic myelopathy - Wang, Xu-xiang; Li, Guang-sheng; Wang, Kang-heng; Hu, Xiao-song; Hu, Yong (Frontiers in Neuroscience, 2024)
The objective was to investigate whether microvascular proliferation could positively affect the neural function recovery in experimental cervical spondylotic myelopathy(CSM). A total of 60 male adult Sprague-Dawley (SD) rats were randomly divided into four groups: Control (CON), Compression (COM), Angiostasis (AS) and Angiogenesis (AG), with 15 rats in each group. Rats in the AS group received SU5416 to inhibit angiogenesis, while rats in the AG group received Deferoxamine (DFO) to promote angiogenesis. Motor and sensory functions were assessed using Basso Beattie Bresnahan (BBB) scale and Somatosensory Evoked Potential (SEP).Neuropathological degeneration was evaluated by the number of neurons, Nissl bodies(NB) and the demyelination of white matter detected by Hematoxylin&Eosin(HE), Toluidine Blue (TB) and Luxol Fast Blue (LFB) staining. Immunohistochemical (IHC) staining was used to observe the Neurovascular Unit (NVU). Rats in the CON group exhibited normal locomotor function with full BBB score, normal SEP latency and amplitude. Among the other three groups, the AG group had the highest BBB score and the shortest SEP latency, while the AS group had the lowest BBB score and the most prolonged SEP latency. The SEP amplitude showed an opposite performance to the latency.Comparing to COM and AS group, the AG group demonstrated the significant neuronal restoration in gray matter and axonal remyelination in white matter. DFO promoted microvascular proliferation especially in gray matter, and improved the survival of neuroglial cells. In contrast, SU5416 inhibited the viability of neuroglial cells by reducing microvessels. The microvascular status was closely related to NVU remodeling and functional recovery. Therefore, the proliferation of microvessels contributed to functional recovery in experimental CSM, which may be associated with NVU remodeling.